Histological Effect of Antidiabetic Herbal Tea on The Spleen of Albino Rats Induced with Alloxan (Diabetes) - Uwuigbe, Matthew; OHIWEREI, WISDOM; Ogbe, Clementina; Obeagu, Emmanuel; Ohiwerei, Faith (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigated the effects of an anti-diabetic herbal tea on splenic histology and body weight in alloxan-induced diabetic Wistar rats. Thirty rats were divided into five groups (n=6): a positive control (Group A), a negative diabetic control (Group B), and three experimental groups (Groups C, D, and E) that received 3.4 ml, 6.7 ml, and 13 ml of the herbal tea, respectively, for 14 days. Body weight was recorded before and after treatment, and spleen tissues were analyzed histologically with H&E staining. The results showed that the diabetic control group (Group B) had a significant decrease in body weight (p=0.01), while the positive control group (Group A) showed no significant change (p=0.85). In the treatment groups, a low dose (Group C) resulted in a significant weight reduction (p=0.03), whereas higher doses (Groups D and E) showed non-significant trends toward weight loss (p=0.07 and p=0.08, respectively). Histological analysis revealed splenic infarcts and coagulative necrosis in the diabetic control group. The low-dose group (Group C) exhibited inflammatory changes and congestive splenomegaly. In contrast, the moderate-dose group (Group D) showed a near-normal splenic architecture, and the high-dose group (Group E) displayed a preserved fibroelastic capsule. These findings indicate that the anti-diabetic herbal tea has dose-dependent effects on body weight and spleen histology. Specifically, a moderate dose (6.7 ml) restored splenic structure, while a higher dose (13 ml) provided structural protection, suggesting its potential as a therapeutic agent for managing diabetes. The study underscores the importance of proper dosing to optimize therapeutic outcomes.